[Rezension von: Southcombe, George, 1978-, The culture of dissent in restoration England] - Dunan-Page, Anne (A journal of church and state, 2021)
George Southcombe announces various intellectual debts in this volume. The book is structured around case studies: a method, as he reminds us, already employed by Christopher Hill in his Experience of Defeat: Milton and Some Contemporaries (1984). The title sounds a distant echo of N. H. Keeble’s The Literary Culture of Nonconformity in Later Seventeenth-Century England (1987), here qualified as “the best single volume on Restoration dissent” (p. 22), and Southcombe is largely inspired by the “religious turn in the historiography of the Restoration” of the 1990s (p. 3). Other “turns,” by comparison, seem to have been avoided. There are no...